THE AMBIGUITY OF WOMAN TRANSCENDENCE IN ARTHUR GOLDEN’S MEMOIRS OF A GEISHA - Zainil, Camelia Putri (STBA Prayoga Padang, 2023)
Abstract This research analyzes Golden’s Memoirs of a Geisha from feminism perspective. The research objectives are to find out and explain the process that triggers the ambiguity by Chiyo as the main female character. In doing the analysis, this research used qualitative study applying the content analysis method. The data is presented in form of quotation related to woman processes in transcendence that trigger the ambiguity found in the novel. The data analysis was conducted using the library research method to gain information. This research applied descriptive study in textual analysis to analyze the data from the novel. The finding of this research is about the ambiguity of Chiyo’s transcendence. Chiyo is able to achieve her process in transcendence but some effect triggers her process becomes ambiguity. Through the process of transcendence Chiyo becomes gain her independence by opening business but she still is a mistress of her Danna. This condition makes Chiyo process of transcendence becomes ambiguity. She is still trapped in male sexual oppression though she has gained freedom for her financial and status.